Terapi Madu Pada Penderita Ulkus Diabetikum - Ayu Ningsih; Susianti; M. Yusran (CV. Jasa Sukses Abadi, 2019)
Diabetes Mellitus (DM) is a metabolic disorder characterized by high levels of sugar (hyperglycemia) due to decreased insulin secretion by the pancreas, reduced insulin sensitivity, or both. One complication of DM is diabetic ulcer. Diabetic ulcers occur due to reduced vascular supply of blood vessels at the peripheral end resulting in the absence of oxygen so the tissue becomes necrotic. The importance of wound care is important to prevent the occurrence of fatal complications in the form of amputation in response to Wagner 5 criteria. Treatment of wounds in the form of herbal ingredients such as olive oil, honey and aloe vera has been done. Honey has several ingredients that are useful as antibacterial, anti-inflammatory, autolysis and wound healing. while the important enzymes contained in honey are diastase, invertase, glucose oxidase, peroxidase, and lipase. Antibacterial honey has a mixture of 48% sugar and 15-20% moisture content so that the content makes the bacteria unable to live. Honey can activate plasminogen into plasmin, this plasmin will become a fibrin thread which facilitates blood flow. The high glucose level of honey increases glucolysis which produces an energy source for macrophages.